The Influence of Organizational Culture and Leadership style on Employee Performance with Organizational Commitment as Intervening Variable - Galih Arip; Siti Haerani; Muhammad Ismail (Hasanuddin Journal of Business Strategy, 2020)
This study aims to critically examine the application of organizational culture and leadership style carried out by PT Perkebunan Nusantara XIV and its impact on organizational commitment and employee performance. This research was conducted at PT Perkebunan Nusantara XIV by taking data from permanent employees. Data collection was carried out by distributing questionnaires. Data were collected from 213 respondents who were selected using considerations, namely that they must have criteria as permanent employees and have a service period of more than 1 (one) year. The method of analysis is Structure Equation Modeling with the AMOS program version 24.0. The results show that organizational culture and leadership style have a positive and significant influence on organizational commitment. Then, organizational commitment has a positive and significant influence on employee performance. organizational culture has a positive and significant influence on employee performance, but leadership style has no influence on employee performance. In addition, organizational culture and leadership style have a positive and significant influence on employee performance through organizational commitment.